“It's Ok, We're Not Cousins by Blood”: The Cousin Marriage Controversy in Historical Perspective - Paul, Diane B; Spencer, Hamish G (PLOS Biology, 2008)
Marriage between first cousins is highly stigmatized in the West and, indeed, is illegal in 31 US states. But is the hostility to such marriage scientifically well-grounded?